Do Women With High eHealth Literacy Profit More From a Decision Aid on Mammography Screening? Testing the Moderation Effect of the eHEALS in a Randomized Controlled Trial - Reder, Maren; Soellner, Renate; Kolip, Petra (Frontiers in Public Health, 2019)
Background. Our decision aid on mammography screening developed according to the criteria of the International Patient Decision Aids Standards Collaboration increases knowledge compared to usual care. However, it remains unclear whether this decision aid is more effective in women with higher eHealth literacy. Our objective was to test whether the positive effect of the decision aid on knowledge is moderated by eHealth literacy. Methods. 1,206 women aged 50 from Westphalia-Lippe, Germany, participated (response rate of 16.3%) in our study and were randomised to usual care (i.e., the standard information brochure sent with the programme's invitation letter) or the decision aid. eHealth literacy was assessed at baseline with the electronic health literacy scale (eHEALS); knowledge was assessed at baseline and post-intervention. First, we compared the 2-factor model of the German eHEALS (information seeking and information appraisal) found in previous research and the 3-factor model we hypothesized for decision aid use to the originally proposed 1-factor model. Second, we modelled the measurement model according to the superior factor model found in step one and tested whether the eHEALS moderated the effect of the decision aid on knowledge. Results. The 3-factor model of the eHEALS had a better model fit than the 1-factor or 2-factor model. Both information seeking, information appraisal, and information use had no effect on knowledge post-intervention. All three interactions of the decision aid with information seeking, information appraisal, and information use were not significant. Equally, neither education nor its interaction with the decision aid had an effect on knowledge post-intervention. Conclusion. The decision aid developed in this project increases knowledge irrespective of level of eHealth literacy. This means that not only women with high eHealth literacy profit from the decision aid but that the decision aid has been successfully conceptualised as a comprehensible information tool that can be used by women of varying eHealth literacy levels.